Graph Machine Learning Models Applied on the Identification of Critical Transmission Lines in Electrical Power Systems - Alves, Rogerio Jose Menezes (2022)
When the operation of electric power systems is concerned, one may associate security with predicting a future event, and then be always ready to what may happen in the future. Obtaining a more secure system becomes a task deeply entangled with having rob